Deletion of the Voltage-Gated Calcium Channel Gene, CaV1.3, Reduces Purkinje Cell Dendritic Complexity Without Altering Cerebellar-Mediated Eyeblink Conditioning - Annette Klomp; Martha Pace; Jacqueline Mehr; Maria Fernanda Hermosillo Arrieta; Cessily Hayes; Anthony Fleck; Shane Heiney; Aislinn Williams (The Cerebellum, 2025)
Genetic variation in CACNA1D , the gene that encodes the pore-forming subunit of the L-type calcium channel Ca V 1.3, has been associated with increased risk for neuropsychiatric disorders that display abnormalities in cerebellar structures. We sought to clarify if deletion of Ca V 1.3 in mice would induce abnormalities in cerebellar cortex cytoarchitecture or synapse morphology. Since Ca V 1.3 is highly expressed in cerebellar molecular layer interneurons (MLIs) and L-type channels appear to regulate GABA release from MLIs, we hypothesized that loss of Ca V 1.3 would alter GABAergic synapses between MLIs and Purkinje cells (PCs) without altering MLI density or PC structure. As expected, we did not observe changes in the density of MLIs or PCs. Surprisingly, Ca V 1.3 KO mice do have decreased complexity of PC dendritic arbors without differences in the number or structure of GABAergic synapses onto PCs. Loss of Ca V 1.3 was not associated with impaired acquisition of delay eyeblink conditioning. Therefore, our data suggest that Ca V 1.3 expression is important for PC structure but does not affect other measures of cerebellar cortex morphology or cerebellar function as assessed by delay eyeblink conditioning.

The power of hydropeaking: Trade-offs between flexible hydropower and river ecosystem services in Europe - Terese E. Venus; Oreoluwa Ola; Maria Alp; Nico Bätz; Maria Dolores Bejarano; Isabel Boavida; Maria Cristina Bruno; Roser Casas-Mulet; Mauro Carolli; Gabriele Chiogna; Marie-Pierre Gosselin; Jo H. Halleraker; et al. (Ecological Economics, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Effect of photoperiod and temperature on bioproduct production from juvenile sporophytes of Macrocystis pyrifera - Diane Purcell; Thomas T. Wheeler; Maria Hayes; Michael A. Packer (Frontiers in Marine Science, 2024)
The giant kelp ( Macrocystis pyrifera (Linnaeus) C. Agardh 1820) is a habitat-forming brown seaweed in temperate systems with an unexplored potential as a source of seaweed bioproducts. This study used M. pyrifera sporophytes sourced in Tasmania, Australia, to investigate the effect of photoperiod and temperature on growth rates and the nutritional characteristics of the resulting juvenile biomass. Four cultivation treatments combined growth temperatures of 12 °C, 15 °C, 18 °C with light:dark (L:D) of 12:12 and 16:8 (L:D) photoperiods, (12 °C – (12:12); 12 °C – (16:8); 15 °C – (12:12); 18 °C – (12:12) to investigate their effect on the number and size of sporophytes, biomass accumulation and nutritional composition. After 60 days of cultivation the 12 °C – (12:12) treatment had the greatest number of juvenile sporophytes, and the greatest biomass of 14 ± 1.3 g dry weight (DW). The lowest biomass of 1 g DW, was obtained from the 18 °C – (12:12) treatment. The protein content across all treatments ranged from 16-22.48% DW, with the 12 °C (12:12) treatment having largest range, then the 12°C (16:18) treatment was next with 18.48-22.48% DW, and the 15°C (12:12) treatment had the lowest protein range with 16.48-18% DW. These results are in the range of protein content previously reported for brown seaweeds of 5-20%. Total polysaccharide content ranged from 9.6-16.2% DW with the highest content of 16.2% DW obtained for the 15 °C – (12:12) treatment, and the lowest total polysaccharide content of 9.6% DW obtained for the 12 °C (16:18) treatment. After 66 days of cultivation, the highest yield of sulphated polysaccharides of 0.4% DW was obtained for the 12 °C (12:12) treatment. Total fatty acids were analysed, with the highest polyunsaturated fatty acid content of 60.4% detected in the 12 °C (12:12) treatment. This study demonstrates that temperature and photoperiod are factors impacting juvenile sporophyte growth, biomass accumulation and biochemical composition. The study showed the least stressed sporophytes produced the most potentially beneficial nutritional or bioactive profile.

Predicting the loss of forests, carbon stocks and biodiversity driven by a neotropical ‘gold rush’ - William Michael Hayes; Maria Voigt; Isabel Rosa; Kerry Anne Cort; Nic Kotlinski; Michelle Kalamandeen; Zoe Georgina Davies; Jake Emmerson Bicknell (Biological Conservation, 2023)

Multidisciplinary docking, kinetics and X-ray crystallography studies of baicalein acting as a glycogen phosphorylase inhibitor and determination of its’ potential against glioblastoma in cellular models - Rachel T. Mathomes; Symeon M. Koulas; Ioannis Tsialtas; George Stravodimos; Philip J. Welsby; Anna-Maria G. Psarra; Izabela Stasik; Demetres D. Leonidas; Joseph M. Hayes (Chemico-Biological Interactions, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Nosotros mismos nos estamos matando/We are the ones killing ourselves: Unraveling individual and network characteristics associated with negative dietary acculturation among Mexican Americans in New York City - Karen R. Flórez; Brooke M. Bell; Alyshia Gálvez; Maria Hernández; Sandra Verdaguer; Kayla de la Haye (Appetite, 2023)

In vitro enzyme inhibitory effects of green and brown Australian seaweeds and potential impact on metabolic syndrome - Emer Shannon; Michael Conlon; Maria Hayes (Journal of Applied Phycology, 2023)

A circular economy framework for seafood waste valorisation to meet challenges and opportunities for intensive production and sustainability - Ronan Cooney; David Baptista de Sousa; Ana Fernández-Ríos; Sinead Mellett; Neil Rowan; Andrew P. Morse; Maria Hayes; Jara Laso; Leticia Regueiro; Alex HL. Wan; Eoghan Clifford (Journal of Cleaner Production, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Mesopelagic Fish Protein Hydrolysates and Extracts: A Source of Novel Anti-Hypertensive and Anti-Diabetic Peptides - Azza S. Naik; R. D. Whitaker; S. Albrektsen; Runar G. Solstad; Lars Thoresen; Maria Hayes (Frontiers in Marine Science, 2021)
The abundance of fish and zooplankton (1 × 10 9 tons to 7 × 10 10 tons) in the mesopelagic zone of the ocean is a source of novel raw materials that provides opportunities for sustainable new product development. The peculiar conditions of light and pressure in this ecological zone and the position of the specific organisms in the marine food chain results in diversity in their bio-composition. Mesopelagic fish are an underutilized resource, rich in proteins and omega-3 oils, and present opportunities to develop novel feed, food and functional food ingredients and products. However, there is also a need to ensure that this resource is not overfished and is processed to optimize the catch in line with sustainability goals. There is therefore a need to establish sustainable bioprocessing technologies to yield value added products from mesopelagic fish species. In the present study, various protein extracts from the mesopelagic fish Maurolicus muelleri (M) and Meganyctiphanes norvegica (Northern Krill) (K) and combinations of proteins from these species (C) were generated using hydrolysis methods. Protein Hydrolysates were generated using four different enzymes including Alcalase, endocut-01, endogenous M/K enzymes and FoodPro PNL. Hydrolysates were characterized and assessed for their ability to inhibit enzymes important in diseases associated with metabolic syndrome. The ability of generated Hydrolysates to inhibit enzymes including Angiotensin-1-converting enzyme (ACE-1; EC. 3.4.15.1) associated with blood pressure regulation, Acetylcholinesterase (AChE; EC 3.1.1.7) associated with maintenance of the nervous system, and Dipeptidyl peptidase IV (DPP-IV; EC 3.4.14.5) linked with development of type-2-diabetes, was determined. In a separate process, the same mesopelagic fish species were transformed into fishmeal, Hydrolysates, fish-silage, and aqueous extracts (AQ) and screened for bioactivities using the same bioassays. The Hydrolysates contained greater than 60% protein (dry weight basis) when analyzed using the DUMAS method. A hydrolysate from M. muelleri generated using FoodPro PNL (M1) inhibited the ACE-1 enzyme by 89.56% when assayed at a concentration of 1 mg/ml compared to the positive control Captopril © . Aqueous extract two (AQ2) inhibited ACE-1 by 95.28% when assayed at 1 mg/ml compared to the control. Sample M1 inhibited DPP-IV by 100% and aqueous extract one (AQ1) inhibited the same enzyme by 90.08% when assayed at a concentration of 1 mg/ml compared to Sitagliptin used as the positive control. All samples assayed did not significantly inhibit the enzyme AChE–fraction C3 (combined hydrolzate 3: Krill and M. muelleri ) inhibited AChE by 27.48% only. Based on these results samples M1, C3, and AQ1 were selected for further characterization and the IC 50 values for each were determined in relation to ACE-1 and DPP-IV inhibition as well as their amino acid composition. Glutamate and aspartate were the most abundant amino acids in the selected samples. IC 50 values of <0.2 mg/ml and distinct terminal amino acids were identified in each of the three fractions. The study shows that targeting processing of mesopelagic fish have potential to generate Hydrolysates for use in the prevention of type-2-diabetes and hypertension.

The ENIGMA sports injury working group:– an international collaboration to further our understanding of sport-related brain injury - Inga K. Koerte; Carrie Esopenko; Sidney R. Hinds; Martha E. Shenton; Elena M. Bonke; Jeffrey J. Bazarian; Kevin C. Bickart; Erin D. Bigler; Sylvain Bouix; Thomas A. Buckley; Meeryo C. Choe; Paul S. Echlin; et al. (Brain Imaging and Behavior, 2021)
Sport-related brain injury is very common, and the potential long-term effects include a wide range of neurological and psychiatric symptoms, and potentially neurodegeneration. Around the globe, researchers are conducting neuroimaging studies on primarily homogenous samples of athletes. However, neuroimaging studies are expensive and time consuming, and thus current findings from studies of sport-related brain injury are often limited by small sample sizes. Further, current studies apply a variety of neuroimaging techniques and analysis tools which limit comparability among studies. The ENIGMA Sports Injury working group aims to provide a platform for data sharing and collaborative data analysis thereby leveraging existing data and expertise. By harmonizing data from a large number of studies from around the globe, we will work towards reproducibility of previously published findings and towards addressing important research questions with regard to diagnosis, prognosis, and efficacy of treatment for sport-related brain injury. Moreover, the ENIGMA Sports Injury working group is committed to providing recommendations for future prospective data acquisition to enhance data quality and scientific rigor.

Climate‐induced changes in the suitable habitat of cold‐water corals and commercially important deep‐sea fishes in the North Atlantic - Telmo Morato; José‐Manuel González‐Irusta; Carlos Dominguez‐Carrió; Chih‐Lin Wei; Andrew Davies; Andrew K. Sweetman; Gerald H. Taranto; Lindsay Beazley; Ana García‐Alegre; Anthony Grehan; Pascal Laffargue; Francisco Javier Murillo; et al. (Global Change Biology, 2020)
The deep sea plays a critical role in global climate regulation through uptake and storage of heat and carbon dioxide. However, this regulating service causes warming, acidification and deoxygenation of deep waters, leading to decreased food availability at the seafloor. These changes and their projections are likely to affect productivity, biodiversity and distributions of deep‐sea fauna, thereby compromising key ecosystem services. Understanding how climate change can lead to shifts in deep‐sea species distributions is critically important in developing management measures. We used environmental niche modelling along with the best available species occurrence data and environmental parameters to model habitat suitability for key cold‐water coral and commercially important deep‐sea fish species under present‐day (1951–2000) environmental conditions and to project changes under severe, high emissions future (2081–2100) climate projections (RCP8.5 scenario) for the North Atlantic Ocean. Our models projected a decrease of 28%–100% in suitable habitat for cold‐water corals and a shift in suitable habitat for deep‐sea fishes of 2.0°–9.9° towards higher latitudes. The largest reductions in suitable habitat were projected for the scleractinian coral Lophelia pertusa and the octocoral Paragorgia arborea , with declines of at least 79% and 99% respectively. We projected the expansion of suitable habitat by 2100 only for the fishes Helicolenus dactylopterus and Sebastes mentella (20%–30%), mostly through northern latitudinal range expansion. Our results projected limited climate refugia locations in the North Atlantic by 2100 for scleractinian corals (30%–42% of present‐day suitable habitat), even smaller refugia locations for the octocorals Acanella arbuscula and Acanthogorgia armata (6%–14%), and almost no refugia for P. arborea . Our results emphasize the need to understand how anticipated climate change will affect the distribution of deep‐sea species including commercially important fishes and foundation species, and highlight the importance of identifying and preserving climate refugia for a range of area‐based planning and management tools.

The genetics of resistance to lettuce drop (Sclerotinia spp.) in lettuce in a recombinant inbred line population from Reine des Glaces × Eruption - Bullo Erena Mamo; Ryan J. Hayes; Maria José Truco; Krishna D. Puri; Richard W. Michelmore; Krishna V. Subbarao; Ivan Simko (Theoretical and Applied Genetics, 2019)

Production of protein extracts from Swedish red, green, and brown seaweeds, Porphyra umbilicalis Kützing, Ulva lactuca Linnaeus, and Saccharina latissima (Linnaeus) J. V. Lamouroux using three different methods - Hanna Harrysson; Maria Hayes; Friederike Eimer; Nils-Gunnar Carlsson; Gunilla B. Toth; Ingrid Undeland (Journal of Applied Phycology, 2018)

Ecological regime shift drives declining growth rates of sea turtles throughout the West Atlantic - Karen A. Bjorndal; Alan B. Bolten; Milani Chaloupka; Vincent S. Saba; Cláudio Bellini; Maria A. G. Marcovaldi; Armando J. B. Santos; Luis Felipe Wurdig Bortolon; Anne B. Meylan; Peter A. Meylan; Jennifer Gray; Robert Hardy; et al. (Global Change Biology, 2017)
Somatic growth is an integrated, individual‐based response to environmental conditions, especially in ectotherms. Growth dynamics of large, mobile animals are particularly useful as bio‐indicators of environmental change at regional scales. We assembled growth rate data from throughout the West Atlantic for green turtles, Chelonia mydas , which are long‐lived, highly migratory, primarily herbivorous mega‐consumers that may migrate over hundreds to thousands of kilometers. Our dataset, the largest ever compiled for sea turtles, has 9690 growth increments from 30 sites from Bermuda to Uruguay from 1973 to 2015. Using generalized additive mixed models, we evaluated covariates that could affect growth rates; body size, diet, and year have significant effects on growth. Growth increases in early years until 1999, then declines by 26% to 2015. The temporal (year) effect is of particular interest because two carnivorous species of sea turtles—hawksbills, Eretmochelys imbricata, and loggerheads, Caretta caretta —exhibited similar significant declines in growth rates starting in 1997 in the West Atlantic, based on previous studies. These synchronous declines in productivity among three sea turtle species across a trophic spectrum provide strong evidence that an ecological regime shift ( ERS ) in the Atlantic is driving growth dynamics. The ERS resulted from a synergy of the 1997/1998 El Niño Southern Oscillation ( ENSO )—the strongest on record—combined with an unprecedented warming rate over the last two to three decades. Further support is provided by the strong correlations between annualized mean growth rates of green turtles and both sea surface temperatures ( SST ) in the West Atlantic for years of declining growth rates ( r = −.94) and the Multivariate ENSO Index ( MEI ) for all years ( r = .74). Granger‐causality analysis also supports the latter finding. We discuss multiple stressors that could reinforce and prolong the effect of the ERS . This study demonstrates the importance of region‐wide collaborations.

Native egg parasitoids recorded from the invasive Halyomorpha halys successfully exploit volatiles emitted by the plant–herbivore complex - Gabriele Rondoni; Valeria Bertoldi; Robert Malek; Maria Cristina Foti; Ezio Peri; Lara Maistrello; Tim Haye; Eric Conti (Journal of Pest Science, 2017)

GDF11 Treatment Attenuates the Recovery of Skeletal Muscle Function After Injury in Older Rats - Yu Zhou; Neel Sharma; David Dukes; Maria B. Myzithras; Priyanka Gupta; Ashraf Khalil; Julius Kahn; Jennifer S. Ahlberg; David B. Hayes; Michael Franti; Tracy Criswell (The AAPS Journal, 2017)

Novel Dipeptidyl Peptidase IV Inhibitory and Antioxidant Peptides Derived from Human Gastrointestinal Endogenous Proteins - Lakshmi A. Dave; Maria Hayes; Paul J. Moughan; Shane M. Rutherfurd (International Journal of Peptide Research and Therapeutics, 2016)

Small Molecule Specific Run Acceptance, Specific Assay Operation, and Chromatographic Run Quality Assessment: Recommendation for Best Practices and Harmonization from the Global Bioanalysis Consortium Harmonization Teams - Eric J. Woolf; Stuart McDougall; Douglas M. Fast; Maristela Andraus; Matthew Barfield; Michael Blackburn; Ben Gordon; David Hoffman; Noriko Inoue; Gabriel Marcelin-Jimenez; Amy Flynn; Richard LeLacheur; et al. (The AAPS Journal, 2014)

Contemporary Rates of Carbon Sequestration Through Vertical Accretion of Sediments in Mangrove Forests and Saltmarshes of South East Queensland, Australia - Catherine E. Lovelock; Maria Fernanda Adame; Vicki Bennion; Matthew Hayes; Julian O’Mara; Ruth Reef; Nadia S. Santini (Estuaries and Coasts, 2014)

Diet and the risk of head and neck cancer: a pooled analysis in the INHANCE consortium - Shu-Chun Chuang; Mazda Jenab; Julia E. Heck; Cristina Bosetti; Renato Talamini; Keitaro Matsuo; Xavier Castellsague; Silvia Franceschi; Rolando Herrero; Deborah M. Winn; Carlo La Vecchia; Hal Morgenstern; et al. (Cancer Causes & Control, 2012)

An examination of male and female odds ratios by BMI, cigarette smoking, and alcohol consumption for cancers of the oral cavity, pharynx, and larynx in pooled data from 15 case–control studies - Jay H. Lubin; Joshua Muscat; Mia M. Gaudet; Andrew F. Olshan; Maria Paula Curado; Luigino Dal Maso; Victor Wünsch-Filho; Erich M. Sturgis; Neonilia Szeszenia-Dabrowska; Xavier Castellsague; Zuo-Feng Zhang; Elaine Smith; et al. (Cancer Causes & Control, 2011)

The inheritance of resistance to Verticillium wilt caused by race 1 isolates of Verticillium dahliae in the lettuce cultivar La Brillante - Ryan J. Hayes; Leah K. McHale; Gary E. Vallad; Maria Jose Truco; Richard W. Michelmore; Steve J. Klosterman; Karunakaran Maruthachalam; Krishna V. Subbarao (Theoretical and Applied Genetics, 2011)

Limits of life in MgCl 2 ‐containing environments: chaotropicity defines the window - John E. Hallsworth; Michail M. Yakimov; Peter N. Golyshin; Jenny L. M. Gillion; Giuseppe D'Auria; Flavia De Lima Alves; Violetta La Cono; Maria Genovese; Boyd A. McKew; Sandra L. Hayes; Gayle Harris; Laura Giuliano; et al. (Environmental Microbiology, 2007)
Summary The biosphere of planet Earth is delineated by physico‐chemical conditions that are too harsh for, or inconsistent with, life processes and maintenance of the structure and function of biomolecules. To define the window of life on Earth (and perhaps gain insights into the limits that life could tolerate elsewhere), and hence understand some of the most unusual biological activities that operate at such extremes, it is necessary to understand the causes and cellular basis of systems failure beyond these windows. Because water plays such a central role in biomolecules and bioprocesses, its availability, properties and behaviour are among the key life‐limiting parameters. Saline waters dominate the Earth, with the oceans holding 96.5% of the planet's water. Saline groundwater, inland seas or saltwater lakes hold another 1%, a quantity that exceeds the world's available freshwater. About one quarter of Earth's land mass is underlain by salt, often more than 100 m thick. Evaporite deposits contain hypersaline waters within and between their salt crystals, and even contain large subterranean salt lakes, and therefore represent significant microbial habitats. Salts have a major impact on the nature and extent of the biosphere, because solutes radically influence water's availability (water activity) and exert other activities that also affect biological systems (e.g. ionic, kosmotropic, chaotropic and those that affect cell turgor), and as a consequence can be major stressors of cellular systems. Despite the stressor effects of salts, hypersaline environments can be heavily populated with salt‐tolerant or ‐dependent microbes, the halophiles. The most common salt in hypersaline environments is NaCl, but many evaporite deposits and brines are also rich in other salts, including MgCl 2 (several hundred million tonnes of bischofite, MgCl 2 ·6H 2 O, occur in one formation alone). Magnesium (Mg) is the third most abundant element dissolved in seawater and is ubiquitous in the Earth's crust, and throughout the Solar System, where it exists in association with a variety of anions. Magnesium chloride is exceptionally soluble in water, so can achieve high concentrations (> 5 M) in brines. However, while NaCl‐dominated hypersaline environments are habitats for a rich variety of salt‐adapted microbes, there are contradictory indications of life in MgCl 2 ‐rich environments. In this work, we have sought to obtain new insights into how MgCl 2 affects cellular systems, to assess whether MgCl 2 can determine the window of life, and, if so, to derive a value for this window. We have dissected two relevant cellular stress‐related activities of MgCl 2 solutions, namely water activity reduction and chaotropicity, and analysed signatures of life at different concentrations of MgCl 2 in a natural environment, namely the 0.05–5.05 M MgCl 2 gradient of the seawater : hypersaline brine interface of Discovery Basin – a large, stable brine lake almost saturated with MgCl 2 , located on the Mediterranean Sea floor. We document here the exceptional chaotropicity of MgCl 2 , and show that this property, rather than water activity reduction, inhibits life by denaturing biological macromolecules. In vitro , a test enzyme was totally inhibited by MgCl 2 at concentrations below 1 M; and culture medium with MgCl 2 concentrations above 1.26 M inhibited the growth of microbes in samples taken from all parts of the Discovery interface. Although DNA and rRNA from key microbial groups (sulfate reducers and methanogens) were detected along the entire MgCl 2 gradient of the seawater : Discovery brine interface, mRNA, a highly labile indicator of active microbes, was recovered only from the upper part of the chemocline at MgCl 2 concentrations of less than 2.3 M. We also show that the extreme chaotropicity of MgCl 2 at high concentrations not only denatures macromolecules, but also preserves the more stable ones: such indicator molecules, hitherto regarded as evidence of life, may thus be misleading signatures in chaotropic environments. Thus, the chaotropicity of MgCl 2 would appear to be a window‐of‐life‐determining parameter, and the results obtained here suggest that the upper MgCl 2 concentration for life, in the absence of compensating (e.g. kosmotropic) solutes, is about 2.3 M.

NMDA or AMPA/kainate receptor blockade prevents acquisition of conditioned place preference induced by D2/3 dopamine receptor stimulation in rats - Anna-Maria Biondo; Robert L. H. Clements; David J. Hayes; Brendan Eshpeter; Andrew J. Greenshaw (Psychopharmacology, 2005)